Comparison of Geomembranes Subjected to Differential Settlement. Issue 6 (1st January 1995) - Giroud, J.P.; Soderman, K.L.
Abstract : This technical paper presents a theoretical analysis of the mechanism of deformation of a geomembrane supported by a soil dike and subjected to differential settlement at its connection to a rigid structure. The analysis leads to the development of a new concept, the "co-energy" of the geomembrane tension-strain curve. It is shown that an appropriate way to evaluate and compare the abilities of geomembranes to withstand differential settlement is through the co-energy concept. The use of the co-energy concept is illustrated with a numerical example comparing the abilities of several common geomembrane types to withstand differential settlement.